A Study on the Influence of Artificial Intelligence on Image Art Design - He Jin (SHS Web of Conferences, 2024)
With the continuous development of artificial intelligence technology, the field of video art design is undergoing unprecedented changes. The purpose of this paper is to deeply discuss the influence of artificial intelligence era on video art design. The artificial intelligence generation system can assist in image generation, video processing, 3D modelling and other work, which greatly improves the creation efficiency. At the same time, these systems provide inspiration and creativity to artists by learning and analysing a large number of artworks. In terms of innovation, AI breaks traditional art and design patterns and supports more open and diverse expression. Machine learning-based generation systems can create stunning, novel images and videos that demonstrate creativity beyond imagination. Artificial intelligence inspires us to reflect on the subjectivity of aesthetic standards and to appreciate more the unique aesthetic orientation of algorithms. Ai is having a profound impact on artists, designers and society, and every aspect of life in the future will be dependent on AI.